2016
DOI: 10.15366/rimcafd2016.63.007
|View full text |Cite
|
Sign up to set email alerts
|

Relación entre autoconcepto físico, ansiedad e IMC en estudiantes universitarios mexicanos / The Relation of Physical Self-Concept, Anxiety, and BMI Among Mexicam University Students

Abstract: RESUMENEl propósito de la investigación es conocer y relacionar los resultados del autoconcepto físico, con diferentes tipos de ansiedad y el IMC en los estudiantes de enfermería y educación física dela península de Yucatán (México). La muestra estuvo formada por 264 participantes, de los cuales 91 eran varones y 173 mujeres, con edades comprendidas entre 18 y 25 años. Nuestros datos revelan que en el autoconcepto físico, los valores obtenidos por los estudiantes de educación física son superiores al de los es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…It is important to pay attention to your emotions, because not doing so can lead to some symptoms of depression. In terms of the physical self-concept, Linares-Manrique et al ( 2016) [43] states that men have a superior appreciation of themselves in terms of physical ability, physical condition, strength, and physical attractiveness.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to pay attention to your emotions, because not doing so can lead to some symptoms of depression. In terms of the physical self-concept, Linares-Manrique et al ( 2016) [43] states that men have a superior appreciation of themselves in terms of physical ability, physical condition, strength, and physical attractiveness.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in the youth population, physical aptitude is another element that promotes anxiety levels [18]. Specifically, within the field of psychology, one of the most studied factors related to physical apprehension is physical self-concept [17].…”
Section: Introductionmentioning
confidence: 99%
“…Self-concept plays a crucial and central role in the development of personality, as noted in the main psychological theories; a positive selfconcept is the basis of good personal, social and professional functioning, depending on it, largely, the personal satisfaction, and feeling good about yourself. In particular, physical self-concept proves to be a good indicator of mental health and adjustment with life (Goñi, 2009, Goñi & Infante, 2010Linares-Manrique et al, 2016;Olmedilla, Ortega-Toro, & Abenza, 2016;Reigal, Videra, Parra & Juárez, 2012) since feeling comfortable with our body helps to generate positive feelings.…”
Section: Introductionmentioning
confidence: 99%